2015
DOI: 10.1590/1677-5449.004015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of great saphenous vein occlusion rate and clinical outcome in patients undergoing laser thermal ablation with a 1470-nm bare fiber laser with low linear endovenous energy density

Abstract: Background Water-specific 1470-nm lasers enable vein ablation at lower energy densities and with fewer side effects because they target interstitial water in the vessel wall. Objectives To determine great saphenous vein (GSV) occlusion rate after thermal ablation with 1470-nm laser using 7W power and to evaluate clinical outcomes and complications. Method Nineteen patients (31 GSVs) underwent thermal ablation. Follow-up duplex scanning, clinical evaluation using the Venous Clinical Severity Score (VCSS), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…It was observed that tumescence had a (non-significant) influence on occlusion rate, contributing to efficacy when used with a conventional fiber and low energy (LEED), which was also observed in a study by Araujo et al, 22 who observed a greater recanalization rate at 6 months using these parameters.…”
supporting
confidence: 58%
“…It was observed that tumescence had a (non-significant) influence on occlusion rate, contributing to efficacy when used with a conventional fiber and low energy (LEED), which was also observed in a study by Araujo et al, 22 who observed a greater recanalization rate at 6 months using these parameters.…”
supporting
confidence: 58%
“…5 Araujo et al 6 also studied EVLT using the 1470 nm wavelength, showing that by employing a low energy density the incidence of complications could be reduced without significantly impacting the clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…The fiber was tractioned manually and continuously, in the caudal direction up to the distal limit of the saphenous vein being treated. 11 After the procedure, dressing was applied, exerting extrinsic compression along the path of the GSV, using cotton wool pads and 7/8 high compression elastic stockings (30-40 mmHg). Patients were discharged from hospital on the same day as the operation, after approximately 2 hours of postoperative observation, with a 5-day prescription for analgesics and nonsteroidal anti-inflammatories.…”
Section: Methodsmentioning
confidence: 99%